Healthcare professionals’ attitudes to mandatory COVID-19 vaccination: Cross-sectional survey data from four European countries - Karlsson Linda Cecilia; Garrison Amanda; Holford Dawn; Fasce Angelo; Lewandowsky Stephan; Taubert Frederike; Schmid Philipp; Betsch Cornelia; Rodrigues Fernanda; Fressard Lisa; Verger Pierre; Soveri Anna (United States, 2025)
Mandatory vaccinations are widely debated since they restrict individuals’ autonomy in their health decisions. As healthcare professionals (HCPs) are a common target group of vaccine mandates, and also form a link between vaccination policies and the public, understanding their attitudes toward vaccine mandates is important. The present study investigated physicians’ attitudes to COVID-19 vaccine mandates in four European countries: Finland, France, Germany, and Portugal. An electronic survey assessing attitudes to COVID-19 vaccine mandates and general vaccination attitudes (e.g. perceived vaccine safety, trust in health authorities, and openness to patients) was sent to physicians in the spring of 2022. A total of 2796 physicians responded. Across all countries, 78% of the physicians were in favor of COVID-19 vaccine mandates for HCPs, 49% favored COVID-19 vaccine mandates for the public, and 67% endorsed COVID-19 health passes. Notable differences were observed between countries, with attitudes to mandates found to be more positive in countries where the mandate, or similar mandates, were in effect. The associations between attitudes to mandates and general vaccination attitudes were mostly small to neglectable and differed between countries. Nevertheless, physicians with more positive mandate attitudes perceived vaccines as more beneficial (in Finland and France) and had greater trust in medical authorities (in France and Germany). The present study contributes to the body of research within social and behavioral sciences that support evidence-based vaccination policymaking.